P380 THE REEL'S SYNDROME : A RARE COMPLICATION AFTER PACEMAKER IMPLANTATION. (18th May 2022) - Fais, L; Floris, R; Orrù, F; Sirigu, F; Marini, R; Melis, P; Mancosu, M; Racis, M; Delogu, G
Abstract: We report the case of a 83–year–old male who underwent single chamber pacemaker implantation in another center for bradyarrhythmia (atrial fibrillation) symptomatic for syncope. A ventricular lead was implanted in the apical septum, the post–procedural posterior–anterior chest radiograph showed correct placement of the leads and generator. Approximately 4 months after the implant, the patient came to our observation for repeated electric pulsations in his left shoulder. The patient was affected by mild dementia and was asymptomatic except for the presenting symptomatology, in particular he denied a history of syncope. The ECG showed arrhythmia due to atrial fibrillation, ventricular undersensing, and lack of ventricular capture (Figure 1 ). The chest X–ray showed the complete dislodgement of the ventricular lead tip apparently into the vein secondary to the rotation of the pulse generator on its transverse axis with consecutive coiling of the lead (Fig. 2 ). These findings were consistent with Reel syndrome The patient was admitted to undergo a lead repositioning attempt in consideration of the recent first implant. During the surgery, however, it was shown that the lead was completely displaced from the venous system, near the pectoral muscle. This extreme dislocation of the lead has been related to the electric pulsations felt by the patient. We proceeded with a new re–implantation of the lead and removal of the previous one. The lead was firmly tied to the pectoral muscle with 2 silk points with slight traction control of optimal fixation. Reel's syndrome is a variant of the better known Twiddler syndrome, characterized by the coiling of catheters along the transverse axis of the pacemaker. It is often a complication due to the manipulation of the generator by the patient, unlike Twiddler syndrome it occurs early and the leads remain intact. This syndrome is one of the most serious complications of pacemaker or defibrillator implants, it can be potentially fatal due to lack of therapy in the case of defibrillators, or asystole in pacemaker–dependent patients.